H2S Protects Against Immobilization-Induced Muscle Atrophy via Reducing Oxidative Stress and Inflammation - Xu, Miaomiao; Liu, Xiaoguang; Bao, Peng; Wang, Yan Jie; Lu, Jianqiang; Liu, Yu Jian (Frontiers in Physiology, 2022)
Chronic inflammation and oxidative stress are major triggers of the imbalance between protein synthesis and degradation during the pathogenesis of immobilization-induced muscle atrophy. This study aimed to elucidate the effects of hydrogen sulfide (H2S), a gas transmitter with potent anti-inflammatory and antioxidant properties, on immobilization-induced muscle atrophy. Mice were allocated to control and immobilization (IM) groups, which were treated with slow (GYY4137) or rapid (NaHS) H2S releasing donors for 14 days. The results showed that both GYY4137 and NaHS treatment reduced the IM-induced muscle loss, and increased muscle mass. The IM-induced expressions of Muscle RING finger 1 (MuRF1) and atrogin-1, two muscle-specific E3 ubiquitin ligases, were decreased by administration of GYY4137 or NaHS. Both GYY4137 and NaHS treatments alleviated the IM-induced muscle fibrosis, as evidenced by decreases in collagen deposition and levels of tissue fibrosis biomarkers. Moreover, administration of GYY4137 or NaHS alleviated the IM-induced inﬁltration of CD45+ leukocytes, meanwhile inhibited the expressions of the pro-inflammatory biomarkers in skeletal muscles. It was found that administration of either GYY4137 or NaHS significantly attenuated immobilization-induced oxidative stress as indicated by decreased H2O2 levels and 8-hydroxy-2’-deoxyguanosine (8-OHdG) immunoreactivity, as well as increased total antioxidant capacity (T-AOC), nuclear factor erythroid-2-related factor 2 (NRF2) and NRF2 downstream anti-oxidant targets levels in skeletal muscles. Collectively, the present study demonstrated that treatment with either slow or rapid H2S releasing donors protected mice against immobilization-induced muscle fibrosis and atrophy. The beneficial effects of H2S on immobilization-induced skeletal muscle atrophy might be due to both the anti-inflammatory and anti-oxidant properties of H2S.